A Precursor Approach to Electrospun Polyaniline Nanofibers for Gas Sensors. Issue 11 (22nd August 2016) - Uh, Kyungchan; Kim, Taegeun; Lee, Chan Woo; Kim, Jong‐Man
Abstract : A new approach to the fabrication of polyaniline (PANI) fibers using t ‐Boc PANI as the conducting polymer precursor is developed. Electrospinning of t ‐Boc PANI in a common organic solvent followed by treatment with HCl results in the conducting (≈20 S cm −1 ) PANI fibers that are successfully used in the detection of gaseous ammonia with a detection limit of 10 ppm. Abstract : Polyaniline (PANI) has served as one of the most promising conducting materials in a variety of fields including sensors, actuators, and electrodes. Fabrication of 1D PANI fibers using electrospinning methods has gained a significant amount of attention. Due to the extremely poor solubility of PANI in common organic solvents, fabrication of electrospun PANI fiber has been carried out either by using corrosive solvents such as H2 SO4 or by electrospinning in the presence of other matrix polymers. Herein, a new approach to the fabrication of PANI fibers using tert ‐butyloxycarbonyl‐protected PANI ( t ‐Boc PANI) as the conducting polymer precursor is reported. The t ‐Boc PANI is soluble in common organic solvents (e.g., chloroform and tetrahydrofuran), and electrospinning of t ‐Boc PANI in those solvents affords nano/micrometer‐sized t ‐Boc PANI fibers. Treatment of the electrospun t ‐Boc PANI fibers with HCl results in the removal of the acid labile t ‐Boc group and the generation of conducting (≈20 S cm −1 ) PANI fibers. The HCl‐doped PANI fibers are successfully used in the detection of gaseous ammonia with a detection limit of 10 ppm.